Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to solve $x^3=-1$? I got following: $x^3=-1$



share|cite|improve this question
It may be interesting to analyze why this method does not produce all results: $x^3=−1$ so $x.x^2=−1∗1$ so x=−1 and/or $x=+1$ and/or $x=−1$, since x can't be both +1 and -1, so x=−1. – NoChance Sep 9 '12 at 8:51
up vote 33 down vote accepted

$x^3+1=0\implies (x+1)(x^2-x+1)=0$

If $x+1=0,x=-1$

else $x^2-x+1=0$ then $x=\frac{1±\sqrt{1-4}}{2\cdot1}=\frac{1±\sqrt3i}{2}$ using the well known Quadratic Formula.

Alternatively, using Euler's identity and Euler's formula like other two solutions, for $x^n=-1=e^{i(2m+1)\pi}$ as $e^{i\pi}=-1$ where $m$ any any integer, $n$ is a natural number .

We know $n$-degree equation has exactly $n$ roots, so the roots of $x^n+1=0$ are $e^{\frac{i(2m+1)\pi}{n}}=\cos\frac{(2m+1)\pi}{n}+i\sin \frac{(2m+1)\pi}{n}$ where $m=0,1,2,...n-1$. It's just customary, not mandatory that we have defined $m$ to assume this range of values, in fact it can assume any $n$ in-congruent values (for example, consecutive values like $r,r+1,...,r+n-1,$ where r is any integer), the reason is explained below.

(1)Using Repeated Root Theorem, let $f(x)=x^n+R$ where $n>1$ and $R ≠ 0\implies x≠0$

So, $\frac{df}{dx}=nx^{n-1}, \frac{df}{dx}=0$ does not have any non-zero root.

Clearly, $f(x)=x^n+R$ can not have any repeated root unless $R=0$

(2)Let $e^{\frac{i(2a+1)\pi}{n}}=e^{\frac{i(2b+1)\pi}{n}}$ $\implies e^{\frac{2i(a-b)\pi}{n}}=1=e^{2k\pi i}$ where $k$ is any integer.

$\implies a-b=kn\implies a≡b\pmod n$, so any $n$ in-congruent values of $m$ will give us essentially the same set of n distinct solutions.

Here $n=3$ so, let's take $m=0,1,2$.

$m=0\implies \cos\frac{\pi}{3}+i\sin \frac{\pi}{3}=\frac{1+i\sqrt3}{2} $

$m=1\implies \cos \pi+i\sin\pi=-1 $

$m=2\implies \cos\frac{5\pi}{3}+i\sin \frac{5\pi}{3}=\frac{1-i\sqrt3}{2} $

share|cite|improve this answer
I think the second factor in your first line should be $x^2-x+1$. – Daryl Sep 8 '12 at 12:32
@Daryl, thanks for identifying the lapsus calami. – lab bhattacharjee Sep 8 '12 at 12:34
Hi, where did you got $x^3+1=(x+1)(x^2-x+1)$? I mean also the site, because I found $x^n-1=(x-1)(x^{n-1}+ \dots +1)$ - – alvoutila Sep 8 '12 at 19:02
$x^3+y^3=(x)^3+(y)^3=(x+y)^3-3xy(x+y)=(x+y)((x+y)^2-3xy)=(x+y)(x^2+y^2-xy)$ – lab bhattacharjee Sep 9 '12 at 3:39

Let $x=a+bi$, where $a$ and $b$ are real. Then $(a+bi)^3 = -1$. Expanding the left-hand side gives $$a^3 +3a^2bi -3ab^2 -b^3i = -1.$$

We can separate the real and imaginary parts of this equation: $$\begin{align} a^3 -3ab^2 & = -1 \\ 3a^2b - b^3 & = 0 \end{align}$$

Taking the obvious $b=0$ solution gives us $a=-1$ and thus the real solution

$$x =-1.$$

So suppose $b\ne 0$. Then the second equation has $3a^2 = b^2$, so $b = \pm a\sqrt3$. Putting $3a^2$ for $b^2$ in the first equation gives $$ a^3 - 9a^3 = -1$$ so $a = \frac12.$ Since $b = \pm a\sqrt3$, we have $b=\pm\frac{\sqrt3}2$. This gives us the other two solutions, namely

$$x=\frac12 \pm\!\frac{\sqrt3}2i.$$

share|cite|improve this answer

Set $\displaystyle x=re^{i \theta}$. So $\displaystyle r^3e^{i3\theta}= x^3= -1= e^{i \pi}$, hence $r^3=1$ and $3 \theta= \pi [2\pi]$. Finally, $r=1$ and $\displaystyle \theta = \frac{\pi}{3} \left[\frac{2\pi}{3} \right]$ so you get three solutions: $$x_1= e^{i \pi/3}= \frac{1}{2}+ i \frac{\sqrt{3}}{2}, \ x_2=e^{-i 2 \pi /3}= \frac{1}{2} - i \frac{\sqrt{3}}{2}, \ x_3= e^{i \pi}=-1.$$

share|cite|improve this answer
What does $3 \theta = \pi[2 \pi]$ and $\theta = \frac{\pi}{3}[\frac{2 \pi}{3}]$ mean? Do they mean $3 \theta = \pi+2 \pi n$ and $\theta = \frac{\pi}{3}+ \frac{2 \pi}{3} n$? – alvoutila Sep 13 '12 at 6:47
It is indeed the correct definition. – Seirios Sep 13 '12 at 8:46
well how do you get $\frac{2 \pi}{3}$, because $\theta = \frac{\pi}{3}, \pi, \frac{5 \pi}{3}, \dots$, but you don't find $\frac{2 \pi}{3}$. – alvoutila Sep 13 '12 at 11:02
Indeed, I forgot a minus. Thank you! – Seirios Sep 16 '12 at 8:15

Observe that $(e^{a i})^3 = e^{3 a i}$ and $-1=e^{\pi i}$.

share|cite|improve this answer




$$x=-1 \quad\text{or}\quad x^2-x+1=0$$

When $$x^2-x+1=0, x= \frac{-1(\pm\sqrt{-3})}{2}$$

$$x= \frac{-1+\sqrt{3}i}{2} \quad\text{and}\quad \frac{-1-\sqrt{3}i}{2}$$

Which is equal to $e^{−i2π/3}$ and $e^{i2π/3}$ respectively.

share|cite|improve this answer

The real solution:

$$x^3+1=0<=>$$ $$x^3=-1<=>$$

Take cube roots of both sides:


Complex solution:

$$x^3+1=0<=>$$ $$x^3=-1<=>$$ $$x^3=|-1|e^{arg(-1)i}<=>$$ $$x^3=e^{(\pi +2\pi k)i}<=>$$

(with k is the element of Z)

$$x=\left(e^{(\pi +2\pi k)i}\right)^{\frac{1}{3}}<=>$$ $$x=e^{\left(\frac{1}{3}\pi +\frac{2}{3}\pi k\right)i}$$

(with k goes from 0 to 3 -> k=0-2)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.